A diversity panorama of Coccinellidae (Coleoptera) from Northeastern Brazil - Duarte-De-Mélo, Jefferson; Almeida, Lúcia Massutti De; Lima, Iracilda Maria De Moura (Zootaxa, 2025)
Northeastern Brazil (NE Brazil) is home to four of the country’s six biomes, namely the Amazônia (tropical rainforest), Caatinga (tropical dry forest), Cerrado (tropical savanna), and Mata Atlântica (seasonal tropical forest). These biomes and their adjacent ecotones exhibit distinctive characteristics. Despite the documentation of seventy species of the family Coccinellidae until mid-2021, comprehensive studies of the Coccinellidae fauna as a whole are still lacking. Therefore, this work aims to provide an overview of the Coccinellidae from NE Brazil, through the evaluation of records from published literature and the material deposited in reference entomological collections. The analysis of the material yielded seven new records of genera for this Brazilian region: Adira Gordon & Almeida, 1986; Harmonia Mulsant, 1846; Novius Mulsant, 1850; Paraneda Timberlake, 1943; Pharoscymnus Bedel, 1906, Pseudoryssomus Gordon, 1974; and Rhyzobius Stephens, 1829. Additionally, Pseudoryssomus and Rhyzobius represent new records for Brazil. The tribes Noviini and Sticholotidini are newly documented in the Northeast. A total of 29 new records of species belonging to the Coccinellidae family have been documented in NE Brazil: Adira obscuracincta (Klug, 1829); Calloeneis roxanne Gordon & Hanley, 2020; Chnoodes nigra Weise, 1895; Chnoodes tarsalis Weise, 1904; Coeliaria castanea Churata-Salcedo & Almeida, 2017; Cryptognatha auriculata Mulsant, 1850; Cyrea maxine Canepari & Gordon, 2016; Delphastus davidsoni Gordon, 1994; Dilatitibialis laterinotata (Brèthes, 1925); Epilachna marginella (Fabricius, 1787); Epilachna spreta Mulsant, 1850; Exoplectra batesii (Crotch, 1874); Exoplectra columba Costa, Almeida & Corrêa, 2008; Gordonoryssomus everardoi Almeida & Santos, 2014; Harmonia axyridis (Pallas, 1773); Hyperaspis conclusa Weise, 1904; Hyperaspis festiva Mulsant, 1850; Hyperaspis scutifera (Mulsant, 1850); Novius cardinalis (Mulsant, 1850); Paraneda pallidula (Mulsant, 1850); Pharoscymnus flexibilis (Mulsant, 1853); Pseudoryssomus brulei Almeida & Santos, 2014; Psyllobora bicongregata Boheman, 1859; Psyllobora consitoides Mader, 1958; Psyllobora lenta Mulsant, 1850; Rhyzobius lophanthae (Blaisdell, 1892); Serratitibia shirley Gordon & Canepari, 2013; Zenoria linteolata Mulsant, 1850; Zenoria revestita Mulsant, 1850. Four of them are new records for Brazil: Cryptognatha auriculata, Pseudoryssomus brulei, Hyperaspis scutifera and Rhyzobius lophanthae. This work enhances the diversity of the Coccinellidae known from NE Brazil by approximately 90% (63 additional species). Consequently, NE Brazil has transitioned from the lowest diversity ranking to the third most diverse region in the country. Ultimately, here is provided a baseline for the study of Coccinellidae from Northeastern Brazil.